PENGARUH AUDIT INTERNAL TERHADAP PENCEGAHAN FRAUD PADA PT POS INDONESIA (PERSERO) KOTA BANDUNG - Azzahar, Hikmah R.; Teram Terawati, Mira; Djuharoh, Aan Siti (Jurnal Nusa Akuntansi, 2024)
This study aims to determine whether there is an influence of internal audit on fraud prevention at PT Pos Indonesia (Persero). To determine the influence between the variables studied, researchers use quantitative methods with descriptive and verifiative analysis. Data collection techniques were used through the distribution of questionnaires to 48 respondents. The data analysis methods used include: simple linear regression analysis, correlation coefficient analysis, hypothesis test with t test, and determination coefficient analysis. The results showed that the internal audit variable had an effect on fraud prevention by 63.6% with the category of strong relationships between variables